2011
DOI: 10.1016/j.ejcb.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine regulates connexins sub-types expressed by hepatocytes

Abstract: Intercellular communication via GAP Junctions plays an important role in tissue homeostasis, apoptosis, carcinogenesis, cell proliferation and differentiation. Hepatocyte connexins (Cx) 26 and 32 levels are decreased during the de-differentiation process of primary hepatocytes in culture, a situation that is also characterised by a decrease in S-Adenosylmethionine (SAMe) levels. In this current study, we show that SAMe supplementation in cultured hepatocytes every 12h, leads to an up-regulation of Cx26 and 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
(71 reference statements)
2
10
1
Order By: Relevance
“…6C). This is consistent with Yamaji et al (2011), who observed that SAMe activated PP2A. Although the effect of SAMe may be via PP2A methylation, this is not the mechanism for MTA, as it was still effective even when its conversion to SAMe was blocked with cycloleucine.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…6C). This is consistent with Yamaji et al (2011), who observed that SAMe activated PP2A. Although the effect of SAMe may be via PP2A methylation, this is not the mechanism for MTA, as it was still effective even when its conversion to SAMe was blocked with cycloleucine.…”
Section: Discussionsupporting
confidence: 79%
“…5B). This is in agreement with Yamaji et al (2011); however, our results conflicted when we tested whether SAMe and MTA's inhibitory effect on b-catenin required GSK3b. Using the GSK3b-specific inhibitor TDZD-8, the ability of SAMe and MTA to lower b-catenin levels was abolished (Fig.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Supplementation of the hepatocyte culture medium with this compound results in elevated Cx32 amounts and counteracts the appearance of Cx43. The latter is due to reduced accumulation of nuclear β -catenin, which in turn negatively affects Wnt signalling-dependent gene transcription of Cx43 (Yamaji et al, 2011).…”
Section: Connexins and Alterations In The Liver Differentiation Statusmentioning
confidence: 99%